Pengaruh Digital Marketing terhadap Keputusan Pembelian Konsumen di Era E-Commerce - Etty Zuliawati Zed; Selvi Indriani; Sefi Fefiana Wati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of digital marketing on consumer purchasing decisions in the e-commerce era. The research method used is a quantitative approach with a questionnaire survey design. Data were collected using a questionnaire distributed to 15 respondents who are active e-commerce users in the Cikarang area. The data analysis technique used is simple linear regression analysis to test the relationship between digital marketing variables as dependent variables and purchasing decisions as independent variables. The results of the study indicate that there is a significant positive influence between digital marketing on purchasing decisions, with a coefficient of determination (R²) of 0.545, which indicates that 54.5% of the variation in digital marketing can be influenced by purchasing decisions. This finding indicates that increasing digital marketing can contribute significantly to consumer purchasing decisions in the e-commerce era. Based on these results, business actors can improve their digital marketing progress to maintain and improve consumer purchasing decisions.